Firm efficiency and board busyness : empirical evidence in Southeast and Northeast Asia - Tan, Khar Mang; Fakarudin Kamarudin,; A.N. Bany-Ariffin,; Norhuda Abdul Rahim, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Drawing on technical efficiency concept, the production of outputs from the inputs of firms is theoretically associated with firm managerial factors. This study therefore attempts to empirically investigate the relationship between board busyness and firm efficiency in selected countries of Southeast and Northeast Asia region for seven years. This study first measures technical efficiency of firms by using non-parametric Data Envelopment Analysis (DEA). Predominantly, this study investigates the proposed relationships of board busyness and firm efficiency by performing panel regression analysis. The results from regression analysis show that the board busyness significantly reduces firm efficiency, supporting the busyness hypothesis. The significant practical implications of study include: firstly, the managers who pursue to enhance firm efficiency in achieving the goals of profit maximization are encouraged to prevent their firms from having busy boards. Secondly, the regulators and policy-makers who intend to prevent the overcommitted issue of busy boards are suggested to review and enforce the restrictions and regulations on board busyness. Thirdly, the potential investors who intend to make investment are urged to consider busy boards as an unfavourable signal.